Optimal control of workpiece thermal state in creep-feed grinding using inverse heat conduction analysis - Gostimirović, Marin (Strojniški vestnik, 2011)
Due to intensive friction between grinding particles and workpiece material, a substantial quantity of thermal energy develops during grinding. Efficient determination of real heat loading in the surface layer of the workpiece material in grinding largely depends on the reliability of basic principles of distribution of heat sources and the character of the temperature field within the cutting zone. Therefore, this paper takes a different approach towards the identification of the thermal state of the creep-feed grinding process by using the inverse problem to approximate heat conduction. Based on a temperature measured at any point within a workpiece, this experimental and analytical method allows the determination of a complete temperature field in the workpiece surface layer as well as the unknown heat flux on the wheel/workpiece interface. In order to solve the inverse heat conduction problem, a numerical method using finite differences in implicit form was used. When the inverse heat conduction problem is transformed into an extreme case, the optimization of heat flux leads to an allowed heat loading in the surface layer of workpiece material during grinding. Given the state function and quality criterion, the control of workpiece heat loading allows the determination of optimal creep-feed grinding conditions for particular machining conditions.
Keywords: globoko brušenje; inverzni prevod toplote; krmiljenje; toplotna energija; toplotni tok